DIALOGUE OF RELIGIONS - Manickam, Thomas (Journal of Dharma, 1983)
"Dialogue" literally means words exchanged between two persons. In common usage it implies the mutual exchange of views of two free persons in the presence of each other with the courage to speak boldly and honestly, what one feels and thinks about the other and the matters that pertain to him, and a readiness to listen patiently and attentively to the views and reactions of the other person. Such an exchange of views provides scope for promoting the right understanding about each other, corrects any distortions about each other’s perceptions of matters that are related to both and, finally, enriches their mutual relationship and thus enables them to grow more fully human, more noble, more refined and even more divine, while sharing mutually these values of life which should underlie every dialogue related to religious matters.